Hubungan Intensitas Penggunaan Media Sosial Terhadap Kestabilan Emosi Pada Anak Usia Remaja: The Relationship between the Intensity of Social Media Use on Emotional Stability in Adolescents - Nurul Namira Zahara; Khrisna Wisnusakti (Sagamedia Indo Press, 2022)
Introduction: Social media is an internet-based media where you can share pictures, videos, writings or information that can be seen by fellow social media users to many people, if the intensity is excessive it can cause addiction for users because the features presented are quite attractive to users. According to data, there is an increase in the use of social media every year, especially in adolescents who have unstable emotions. According to data from the Ministry of Health, it was found that children aged over 15 years experienced emotional disorders. Objective: The purpose of this study was to determine the intensity of social media use and emotional stability in 9th grade adolescent children at Al-Azhary Middle School, Cianjur, and the relationship between the two variables. Methods: The method used is quantitative with a correlation research design using a cross-sectional design. The population in this study were 86 students of grade 9 SMP Al-Azhary Cianjur. The sampling technique used total sampling and the data collection instrument was a questionnaire. Results: It was found that the analysis results obtained as many as 12 (52.2%) respondents with low intensity of use of social media with low emotional stability. Meanwhile, 54 (48.3%) respondents with high intensity of social media use have low emotional stability. The results of statistical tests obtained p-value = 0.003 and OR = 5,500. Conclusion: There is a relationship between the intensity of social media use and emotional stability in adolescent children.